TermFrame: a systematic approach to karst terminology - Vintar, Špela (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2020)
We describe a systematic and data-driven approach to karst terminology where knowledge from different textual sources is structured into a comprehensive multilingual knowledge representation. The approach is based on a domain model which is constructed in line with the frame-based approach to terminology and the analytical geomorphological method of describing karst phenomena. The domain model serves as a basis for annotating definitions and aggregating the information obtained from different definitions into a knowledge network. We provide examples of visual knowledge representations and demonstrate the advantages of a systematic and interdisciplinary approach to domain knowledge.
Keywords: fizična geografija; karst terminology; karstology; krasoslovje; kraška terminologija; physical geography